MATHEMATICAL MODEL OF THE MASS MILITARY SERVICE SYSTEM - Xudoyqulova Sayyora Ismoyilovna (Web of Journals Publishing, 2024)
The department of public service theory of mathematics, among other theories, is widely used in the development of many mathematical and practical problems. This theory is important for its current state of public service, with its consistent mathematical methods aimed at analyzing and drawing conclusions and developing recommendations for service improvement.
Keywords: service, analysis, mathematical model, real system.